Proton emission from the drip-line nuclei I-Bi using the WKB approximation with relativistic mean-field densities *Supported by the Department of Science and Technology, Govt. of India (EMR/2015/002517). (April 2019) - Sahoo, T.; Panda, R. N.; Patra, S. K.
Abstract: We study the properties of proton rich nuclei reported as proton emitters in the region from I to Bi with Z = 53 to 83 and N = 56 to 102 as a crucial application to the existence of exotic nuclei. The effective relativistic mean-field formalism (E-RMF), with NL3, FSUGarnet, G3 and IOPB-I interactions, is adopted for analysis of the ground state properties of proton emitters. Furthermore, in the E-RMF background, the Wentzel-Karmers-Brillouin (WKB) barrier penetration method is used for the calculation of proton emission half-lives. It is found that the calculated half-lives are in good agreement with the experimental results for all emitters considered in this study.